2012
DOI: 10.1007/s12185-012-1189-4
|View full text |Cite
|
Sign up to set email alerts
|

Current and future management of NK/T-cell lymphoma based on clinical trials

Abstract: Recently reported results of well-designed prospective clinical trials for extranodal NK/T-cell lymphoma, nasal type (ENKL) have rapidly changed the management of ENKL. This review will focus on the evidence obtained from prospective clinical trials for ENKL and discuss the most highly recommended current management and future directions for the better management of ENKL. For patients with nasal NK/T-cell lymphoma of stage IE or contiguous stage IIE with cervical node involvement, concurrent chemoradiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 67 publications
1
34
0
3
Order By: Relevance
“…L-asparaginase (L-Asp) and pegaspargase (PEGAsp) are important chemotherapeutic drugs for childhood acute lymphoblastic leukemia (ALL), and clinical trials have also shown that L-Asp treatment improves the outcome of NK/T cell lymphoma (7). The exact molecular events that cause cell death following L-Asp treatment remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…L-asparaginase (L-Asp) and pegaspargase (PEGAsp) are important chemotherapeutic drugs for childhood acute lymphoblastic leukemia (ALL), and clinical trials have also shown that L-Asp treatment improves the outcome of NK/T cell lymphoma (7). The exact molecular events that cause cell death following L-Asp treatment remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…(c) Extranodal PTCL (e.g., ENKL) NK/T-cell lymphoma/leukemia can be classified into leukemic and extra nodal (ENKL) types [83]. We previously showed that up-regulation of miR-21 or miR-155, and down-regulation of miR-150, occur frequently in NK/Tcell leukemia/lymphoma [44,80].…”
Section: Mirna Expression Analysis Against T-cell Lymphomasmentioning
confidence: 99%
“…These miRNAs, respectively, regulate protein tyrosine phosphatases, Pten or Ship1, whose downregulation commonly activates AKT signaling [80]. Downregulation of miR-150 also contributes to cell proliferation and anti-aging via up-regulation of AKT2 or Dyskerin [44,83,84]. A previous review article by our group describes this in greater detail [14].…”
Section: Mirna Expression Analysis Against T-cell Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis for NKTCL patients is poor, with 5‐year progression‐free survival (PFS) and overall survival (OS) rates of approximately 30% and 40%, respectively 9, 10. Historically, the poor outcome and high incidence of resistance to conventional therapy may be associated with overexpression of P‐glycoprotein, a transmembrane pump that transports anthracycline‐based chemotherapeutics and results in multidrug resistance 11, 12, 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%